2023
DOI: 10.3390/ma16041376
|View full text |Cite
|
Sign up to set email alerts
|

Residual Bone Height and New Bone Formation after Maxillary Sinus Augmentation Procedure Using Biomaterials: A Network Meta-Analysis of Clinical Trials

Abstract: Background. Different factors may affect new bone formation following maxillary sinus floor augmentation for the rehabilitation of posterior edentulous maxilla. The purpose of this study was to determine the influence of residual bone height (RBH) on new bone formation after lateral sinus augmentation utilizing different biomaterials, through a network meta-analysis (NMA). Methods. PUBMED, Scopus, and Web of Science electronic databases were searched until 31 December 2022 to obtain relevant articles. A hand s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Bone grafts are divided into four main categories: xenografts, allografts, alloplasts and autologous grafts. Various combinations were studied: recombinant human bone morphogenetic protein-2 in an absorbable collagen sponge carrier, recombinant human platelet-derived growth factor-BB in combination with freeze-dried bone allograft or beta-tricalcium phosphate, autologous cell therapy [ 10 , 11 ]. In most cases, the quantity required for autologous bone is too significant.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Bone grafts are divided into four main categories: xenografts, allografts, alloplasts and autologous grafts. Various combinations were studied: recombinant human bone morphogenetic protein-2 in an absorbable collagen sponge carrier, recombinant human platelet-derived growth factor-BB in combination with freeze-dried bone allograft or beta-tricalcium phosphate, autologous cell therapy [ 10 , 11 ]. In most cases, the quantity required for autologous bone is too significant.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Some clinical protocols [25,26] suggested opting for lateral window maxillary sinus floor elevation when the remaining bone height is <5 mm to avoid the risk of sinus membrane tearing. In a study on the height variation of bone graft materials in the maxillary sinus, Khijimatgar et al [27] found that the height resorption rates of bone graft materials in the group with higher RBH were significantly higher than those in the lower RBH group. However, Taschieri et al [28] studied the impact of RBH on spatial change in bone graft materials after crestal maxillary sinus floor elevation and concluded that RBH did not correlate with the resorption of bone graft materials.…”
Section: Analysis Factors Of Resorption Rates 421 Baselines Analysismentioning
confidence: 99%
“…In the case of sinus-lifting through a lateral approach, sufficient buccal retraction is required for a lateral approach through the buccal vestibule. 8 Therefore, implant placement with sinus augmentation in patients with burn-induced microstomia is very difficult to treat.…”
Section: Case Reportmentioning
confidence: 99%